2010
DOI: 10.1111/j.1747-0803.2010.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fetal Ductus Arteriosus and Its Abnormalities-A Review

Abstract: The ductus arteriosus (DA) is a small vessel with major functional importance for the integrity of the fetal circulation. Technical advances in prenatal diagnostics facilitate appropriate echocardiographic estimation of the ductal flow and its abnormalities. Despite the emerging knowledge of its embryological background and developmental processes during advancing gestation we still have to face unresolved questions regarding the identification and optimal surveillance of fetuses at risk of premature closure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 85 publications
0
30
0
Order By: Relevance
“…The authors found that the right ventricular isovolumetric time was prolonged, the right ventricular ejection time was shortened, and the Tei Index was higher in cases with ductal constriction after indomethacin use by the mother compared to healthy fetuses and those without ductal constriction after indomethacin use 30 . Ductus arteriosus constriction must be distinguished from structural lesions associated with ductus arteriosus agenesis, including certain types of tetralogy of Fallot, truncus arteriosus communis, and pulmonary atresia with an intact ventricular septum 7 , 8 , 19 , 31 , 32 . In most cases of tetralogy of Fallot with absent or dysplastic pulmonary valve syndrome, the ductus arteriosus will be absent, which can be confirmed by detailed 2‐dimensional and color Doppler sonography 32 …”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the right ventricular isovolumetric time was prolonged, the right ventricular ejection time was shortened, and the Tei Index was higher in cases with ductal constriction after indomethacin use by the mother compared to healthy fetuses and those without ductal constriction after indomethacin use 30 . Ductus arteriosus constriction must be distinguished from structural lesions associated with ductus arteriosus agenesis, including certain types of tetralogy of Fallot, truncus arteriosus communis, and pulmonary atresia with an intact ventricular septum 7 , 8 , 19 , 31 , 32 . In most cases of tetralogy of Fallot with absent or dysplastic pulmonary valve syndrome, the ductus arteriosus will be absent, which can be confirmed by detailed 2‐dimensional and color Doppler sonography 32 …”
Section: Discussionmentioning
confidence: 99%
“…20 Prenatal constriction of the ductus arteriosus is typically associated with hypertrophy of the RV, right heart dilatation, tricuspid and pulmonary regurgitation, and functional pulmonary atresia. 5,7,13,[21][22][23] Sonographic criteria for diagnosis of ductal constriction include RV and LV enlargement, tricuspid valve regurgitation, a decreased RV shortening fraction or ejection force, a ductus arteriosus PI of less than 1.9, ductus arteriosus PSV values above the 95th percentile adjusted for gestational age, ductus arteriosus peak diastolic velocity values above the 95th percentile adjusted for gestational age, and an hourglass appearance of the ductus arteriosus on 2dimensional echocardiography. 24,25 The sonographic findings in our cases were similar to those described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of fetal echocardiography, various abnormalities of the DA have been described 1). Among ductal diseases in the fetus, ductal constriction or premature closure is one of the most important diseases because it is associated with significant morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Premature closure of the ductus is diagnosed when there is no luminal patency and no flow through the ductus. Premature closure should be differentiated from absence of the ductus 1). Ductal absence is thought to be an early developmental anomaly and is associated with certain cardiac anomalies such as absent pulmonary valve syndrome and truncus arteriosus.…”
Section: Discussionmentioning
confidence: 99%